Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 2209882 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present" ] } The dataset includes 2209882 records from 27851 constituent datasets: 3310 records from Dados da ocorrência de plantas lenhosas em uma cronossequência em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1968 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 270287 records from R. L. McGregor Herbarium Vascular Plants Collection. 13 records from Coccolith counts of multinet M32/5_MSN988. 1140 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 33743 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2316 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 183 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 214 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 15 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 498 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 20520 records from University of Guam Insect Collection. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 2814 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 208 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 7 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 22 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1189 records from UWIZM Molluscs. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4083 records from MCP-Aves - Coleção de Aves. 74 records from Área Selva de Florencia- Cantidad de área ocupada selva_2018. 1 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 135 records from Nannofossil abundance of Hole 36-329. 39 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 3 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 7214 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1058 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 306 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10788 records from Collections of Bioclass, school #179, Moscow. 580 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 704860167 records from EOD - eBird Observation Dataset. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 6 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 206 records from Gross body measurements of Antarctic Rock Cod (Trematomus bernacchii) collected at sites adjacent to Casey Station 2012/13. 4 records from Dinoflagellate abundance of Hole 14-144. 282 records from Middlebury College Bee Collection. 8 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 277417 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 953 records from Occurrence of bees along grazing and agricultural gradients in Northern Tanzania. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 167 records from Total foraminifera counts of multinet M21/6_MSN787. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 160 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 184 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 8 records from Benthic macrofauna abundance of sediment core 12930-063. 10562 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 13 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 35 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 193 records from Données naturalistes de Ingénieurs écologues GEREA. 1 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 9 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 8046 records from sediment metagenome Metagenome. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 1633 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 14 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 3 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 1709 records from suspended particulate matter Raw sequence reads. 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 207 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 32 records from Antarctic Pycnogonids II. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 105 records from Microfossil abundance of Hole 18-173. 1456 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 539 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 2560 records from Upper Silesian Museum, Bird Observations. 252 records from Total foraminifera counts of multinet M6/7_MSN91. 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 269 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 37666 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 28745 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 158115 records from The Himalayan Uplands Plant database (HUP Version 1). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 131 records from Artenvielfalt auf dem Schulgelände. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 58 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 478 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 5335 records from Marine metagenome ICM_JRV. 188 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 146 records from Données de la naturaliste Laurence Beauchamp. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 2 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 15 records from Données naturalistes de ROLLAND Blandine. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 50 records from La Paya, censo rápido de la flora de Jirijiri. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 8 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6192 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 8 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 112523 records from Ocean Salmon Program - Barkley Sound Juvenile Salmon Study from 1987 to 1994. 6 records from Coccoliths in sediment core PS1532-9. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 57913 records from Fichier communal des ongulés. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 90 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 15 records from Nannofossil abundance of Hole 4-25. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5676 records from SNH Bat Casework records 1970-2007. 6 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1708 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 115 records from Living Cirripedia. 1284 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 5 records from Nannofossil abundance of Hole 6-53A. 12 records from Nannofossil abundance of Hole 29-283A. 5129 records from Spider Mites Collection of Jean Gutierrez. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 26 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 6 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 439 records from Implementación de la bioindicación en el Río Magdalena - 2015. 1127 records from marine sediment metagenome Metagenome. 9883 records from University of Nebraska State Museum Birds Collection. 2 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 30313 records from University of California Santa Barbara Invertebrate Zoology Collection. 14 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 2227 records from IRAD Cameroon insect collection. 394 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 627 records from Occurrence of bird species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 292 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 157 records from Nannofossil abundance of Hole 94-610B. 20170 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 100 records from Total foraminifera counts of multinet M21/2_MSN644. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 137 records from Hartland Nature Club Lepidoptera Collection. 86027 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 8 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 80315 records from Fish specimens of Kagoshima University Museum. 2 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 3825 records from UTEP Invertebrates (Arctos). 7 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 4 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 4 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 24020 records from AMNH Bird Collection. 2756 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 2 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from the foothills of the Serranía de San Lucas, Norosí-Colombia. 413272 records from DATAVES. 108 records from Projet Diable de mer - AILERONS. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 14 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 3 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 4975 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 41 records from Planktic foraminifera abundance of Hole 73-524. 6 records from Planktic foraminifera abundance of Hole 53-418B. 19 records from Distribution Data for Megachile chomskyi. 352 records from Flora vascular y no vascular: expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 14 records from Berea College, Ralph L. Thompson Herbarium. 1012 records from Programme ACT : Répartition Merle noir 2011 - 2015 Coordonnées GPS Lambert 93. 11 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 409 records from Distribution of nanoplankton at trap WR2. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 382 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 141813 records from Fermanagh Flora. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 15397 records from Macrophyte Lake Data. 78 records from Données de la naturaliste Anna Even. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 4484 records from Siliceous microfossil occurrence, Site 177-1091. 1 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 59 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 596 records from Range table from benthic foraminifers in ODP Hole 149-900A. 116 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservación Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 111 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 445 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 79 records from Diatom abundance of Hole 95-613. 49618 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 8 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 2987 records from University of Vermont, Pringle Herbarium, Algae Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 234 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 44 records from Description of lithologic section units of IODP Hole 325-M0041A. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 59 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 4510 records from Carabidae of the Carpathians. 1 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 2591 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2779561 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 15645 records from Canadian Lakes Loon Survey. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 403 records from Alan Wormington Collection. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 642 records from Protistan plankton diversity along salt gradient. 5 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 128 records from Pollen profile 2 from Richland Creek. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1878 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 78893 records from Inventaire de la flore de Dordogne 2017. 4072 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 3572 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 7283 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 47167 records from TNHC Herpetology Collection. 1292 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 143 records from Foraminifera abundance of Hole 48-406. 354 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 1117770 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 69 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 623 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel (Plantas). 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 313 records from Benthic foraminifera abundance of Hole 82-558. 722 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 1069 records from DMNS Egg Collection (Arctos). 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 4 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1009 records from Study on plankton at the port of Ostend in 1965. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 162 records from Inventario forestal de una parcela permanente de restauración en el Parque Nacional Natural Alto Fragua Indi Wasi, en la vereda La Estrella, Caquetá. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 5750 records from Vegetation Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2020). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 72 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1702 records from BioGIS - Bryophytes - HUJ collections. 1 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 46316 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 457 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 27019 records from The Brown University Foraminiferal Data Base (BFD). 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 731 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 763 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 34 records from National System of Protected Areas in Poland - Fungi. 64 records from Pilzlehrwald. 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 106 records from Abundance of radiolaria at station UT99-5-1. 144 records from Données naturalistes de Xavier BONNET. 16 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 122412 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 44 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 1015 records from Programme ACT : Répartition Merle noir 2005 - 2009 Coordonnées GPS Lambert 93. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 103 records from Foraminifera species abundances from tow TT011_5-MOC63. 7 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 3 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 2439 records from Flore des Pyrénées. 164 records from Total foraminifera counts of multinet M6/7_MSN100. 20 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 8858 records from Données naturalistes de Benoit MARTHA. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 121259 records from Observations occasionnelles Parc national des Pyrénées. 1 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 2 records from Molecular phylogenetics, PCA, and MFA recover a new species of Cyrtodactylus (Squamata: Gekkonidae) from an isolated sandstone massif in northwestern Cambodia. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 2 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 51 records from Records of the Victorian Conservation Seedbank. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 14 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 4616 records from Inventaire de la flore du Grand Poitiers 2009. 16426 records from Polish gene bank – passport data of plants accessions which are important in human life. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1461 records from M. Gollop Collection. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1498 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 4 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 3 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 673 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 13977 records from Flora of the Korean Peninsula. 15198 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1889 records from Modelaje de la Distribución geográfica de Pinus pseudostrobus y P. leiophylla. 276 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 14365 records from Cowan Tetrapod Collection - Mammals. 11 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 911 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 825 records from Pollen profile ADR309. 102 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 332 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 23829 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 4780 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 281 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 73531 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 14980 records from Données Entomologiques A. HORELLOU 1988-2018. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 321 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1892 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 1461 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 12 records from Planktic foraminifera abundance of Hole 6-47. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 51 records from Nannofossil abundance of Hole 20-199. 565 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 232 records from Planktic foraminifera abundance of Hole 21-207. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 160 records from Données espèces - Expertise IPE 37. 431 records from Nannofossil abundance of Hole 74-528A. 11321 records from WOLL AVH data. 12648 records from Recensement des espèces en vue de l'élaboration du répertoire des forêts sacrées, forêts galeries, savanes et autres formation floristique du Bénin.. 2 records from A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from Maria Cleofas Island, Nayarit, Mexico. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 154 records from Shannon Index and species richness for arthropods. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 67 records from Área Las Hermosas - Cantidad area ocupada oso, 2018. 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 2563 records from Phenological Center - Plants (Laplandskiy). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 572 records from Benthic foraminifera abundance of Hole 84-567A. 313 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 4798 records from ICEL (Land - Invertebrates). 25219 records from UTEP Herpetology (Arctos). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 11874 records from Biological Reference Collections ICM-CSIC. 2 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 127 records from Total foraminifera counts of multinet POS247/2_MSN1380. 2497 records from Données des collections d'algues du MNHN. 54 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 2346 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 137 records from Lynx 2011 présence Occasionnelle Maille 10km Réseau Loup-Lynx ONCFS. 723 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 104 records from Urwald 1 (Bad Waldsee). 421965 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 341 records from Planktic foraminifera abundance of Hole 9-78. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6950 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 6 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 115 records from Total foraminifera counts of multinet M21/4_MSN694. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 817 records from DOW-2. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 122 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 2099 records from BioBlitz Barcelona 2010-14. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 9 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 245 records from Planktic foraminifera counts of sediment core V14-77. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 126 records from Bryological collection of Yugra State University. 7 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 267172 records from hymenoptera. 131 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 1110 records from FFH-Gebiet "Calwer Heckengäu". 60 records from Amphibian and Reptilian (KIEE-AR). 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 858 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 20 records from Birds - Wild Birds (KIDR-BI). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 18 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 81532 records from Bob Merritt Coleoptera Dataset. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 5 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 83 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 14141 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 1044940 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 44 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 3 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 1 records from The Lanternfly genus Polydictya (Hemiptera: Fulgoromorpha: Fulgoridae) from Sulawesi and neighbouring islands, with the description of three new species. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1893 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 13 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 612 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 1014 records from Programme ACT : Répartition Merle noir 2009 - 2013 Coordonnées GPS Lambert 93. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 16119 records from marine metagenome Metagenome. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 10 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-129BX. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 77 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 1 records from Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 62 records from Sibojaï_2017_12_18. 179 records from Ictiofauna de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 151 records from Meetnetten.be - Fyke counts for Amphibia in Flanders, Belgium. 277 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 37479 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 6295 records from Los mamíferos del estado de Durango, México. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 25 records from Schwedische Oribatei (Acari). III.. 23 records from (Table 1) Distribution of palynomorphs in ODP Hole 123-765C. 30 records from MVZ Herp Observations (Arctos). 91 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 336 records from Distribution of xylotrophic fungi of the genus Daedaleopsis in the Asian part of Russia from 1978 to 2019. 6 records from Foraminifera abundance of Hole 58-442. 50 records from (Table 1) Time series of ostracod population density off Bokniseck shore ('Hausgarten'), western Baltic Sea. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 80 records from Total foraminifera counts of multinet M12/3_MSN562. 7598 records from (Table 1) Stratigraphic occurrence of selected diatom species from ODP Hole 105-647A. 21808 records from Banksia Atlas. 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 13 records from Coleção de Coleoptera da Universidade de Brasília. 45 records from Herpetofauna de la expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 642 records from Twenty-two new species in the genus Hyphantrophaga Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, with a key to the species of Mesoamerica. 98 records from Warnowtal (Rostock). 3 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2747 records from Compost microbe establishment and growth in agricultural soils. 202114 records from National Benthic Inventory. 1839 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 16 records from Phenological Center - Fishes (Murmansk). 243 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 6 records from HSU Wildlife Birds. 14484 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 35 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 3436 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 217024 records from Odonata Central. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 3 records from Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners. 119 records from Baltic Sea Basin sediments diversity Raw sequence reads. 1660 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 1 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 89048 records from Mammalogy Collection - Royal Ontario Museum. 2998 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 75 records from Total foraminifera counts of multinet POS231/3_MSN1335. 11 records from Contribution to the taxonomic knowledge of Ampharetidae (Annelida) from Antarctica with the description of Amage giacomobovei sp. nov.. 97 records from CBCGDF CCAfa Volunteer Observation Archive. 197 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 7 records from Parascolopsis akatamae, a new species of dwarf monocle bream (Perciformes Nemipteridae) from the Indo-West Pacific, with redescription of closely related species P. eriomma. 243726 records from Carnet B Lorraine. 29 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 51 records from Nannofossil abundance of Hole 74-526C. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 2887 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 2993 records from Données naturalistes d'Emmanuel SECHET. 360956 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 22 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1337. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 770 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 79 records from BIRDRACE Blinde Hühner. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 8 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 5592 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 17 records from Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species. 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 138 records from Planktic foraminifera abundance of Hole 18-178. 7547 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 1183 records from Soil Invertebrates Surveys from the Chronicle of Nature of the Prioksko-Terrasnyi Biosphere Reserve. 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 119 records from Distribution of planktonic foraminifera of sediment core SH1972_16. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 99 records from Planktic foraminifera abundance of Hole 27-262. 7 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 16 records from Insect Collections of Okomu National Park- Nigeria. 279489 records from ARABEL - Arachnologia Belgica. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 494 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 2848 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 2604 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 348 records from Antarctic pycnogonids. 60949 records from MLZ Bird Collection (Arctos). 15 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6 records from 2. Donauinsel bei Entau. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 43 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 284 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1163 records from Ornithologie Federsammlung - SNSD. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 381 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 46 records from Liether Park (LMS), 5a. 2314 records from Midden-Limburg Fish Ponds Survey. 81595 records from Herbarium (ICEL). 64954 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 8654 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10283 records from Inventario de Hymenóptera; parasítica en México. 64 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 4130 records from UAM Herbarium (ALA), Algae Collection (Arctos). 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 1785 records from 3Soil16S. 59733 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 2579 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 30 records from Nannofossil abundance of Hole 24-233A. 470 records from Gross body measurements of Laternula elliptica collected from sites adjacent to Casey Station 2014/15. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 2 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 193 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 1 records from Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar. 27 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 2 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 193 records from Planktic foraminifera counts of sediment core RC11-134. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 475 records from Planktic foraminifera counts of sediment core A15-558. 9 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 102 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 136 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 445 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 7122 records from Whale catches in the Southern Ocean. 6 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 14860 records from Floristic diversity of the protected areas of Mont Kouffé and Wari Maro in the north of Benin. 1 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 134 records from Mycoblitz 2017 - IRBV et Cercle des Mycologues de Montréal. 230 records from Biometría peces Parque Nacional Natural La Paya. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1933 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 417 records from Benthic foraminifera counts of sediment core GIK23351-1. 11 records from Benthic macrofauna abundance of sediment core 13077-063. 1802 records from Diatomeas bentónicas de los oasis de Baja California Sur. 4587 records from WII Herbarium Dataset. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 24284 records from Quaid-i-Azam University Herbarium. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 756 records from (Table 4) New palynological record of sediments from Odderade. 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 1709627 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 118 records from Nezara viridula records held by the Royal Horticultural Society. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 790 records from Occurrence of insect species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 931 records from South American Antarctic Marine Biodiversity Literature. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 472 records from Blue Mountains Swamp Archaea. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 286 records from California State University, Long Beach Birds. 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 30131 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 384 records from Marine metagenome ICM_AWP. 33 records from Occurrence of mammalia relicts at site Sveduv stul. 3588 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2994 records from Distribution of planktic foraminifera of sediment core M35027-1. 20859 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 121 records from Foraminifera abundance of sediment core IN68-28. 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from Molecular circumscription of new species of Gyrocotyle Diesing, 1850 (Cestoda) from deep-sea chimaeriform holocephalans in the North Atlantic. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 27 records from Planktic foraminifera abundance of Hole 27-260. 133212 records from Arizona State University Hasbrouck Insect Collection. 8 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 40192 records from Flora of the Korean Peninsula Phase II. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 5703 records from MICA - Muskrat occurrences collected by VMM in Flanders, Belgium. 10 records from Occurrence of mammalia relicts at site Dorog. 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 4 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 323 records from Nannofossil abundance of Hole 78-542. 126 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 143 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 128 records from Inventaire des reptiles 2014. 8 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 133 records from Recolección de frutos para evaluar su potencial de germinación en tres estados de maduración (inmaduro, intermedio y maduro). 2 records from Two new charismatic Pristimantis species (Anura: Craugastoridae) from the tepuis of “ The Lost World ” (Pantepui region, South America). 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 2969 records from Cladocera distribution updates 2014. 2 records from Two new species of Lauratonema (Nematoda: Lauratonematidae) from the intertidal zone of the East China Sea. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 82 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 20440 records from Inventaire de la flore de Charente-Maritime 2017. 22 records from Vom Wert alter Amateursammlungen - vier Spinnenarten neu für die Schweiz in der Sammlung Ketterer. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 2 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 1290 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 669 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 462 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 5 records from Megymenum tuberculatum, a new species of Megymenini from Java and a review of distribution of M. brevicorne (Hemiptera: Heteroptera: Dinidoridae). 160 records from Duck sightings per month, Macquarie Island. 248 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 155 records from artsprosjektet_45-15_helvella. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 36 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 4217 records from Caracterización florística de las Sabanas del Yarí en el municipio de La Macarena, Meta. 1254 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT University Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 433 records from Automatic acoustic Monitoring and Inventoring of BIODiversity. 89 records from Faunal assemblage of sediment core TR149-32. 10 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3107 records from Herpetile collection NTNU University Museum. 113 records from Size of planktic foraminifera at CTD station PS55/084-1. 1861 records from Données du naturaliste DELAPRE Jean-Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 3002 records from Colección de Peces Universidad Católica de Oriente. 156 records from (Table 2) Sediment constituents and quartz in the sand-sized fraction, West Florida slope and Eastern Mississippi Fan, during USGS R/V Gyre cruises G80-6A and G81-8. 1 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 11451 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 140 records from Swedish Malaise Trap Project (SMTP) - Braconidae: Cheloninae: Adelius. 210 records from Planktic foraminifera abundance of Hole 4-30. 390 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE272. 14 records from Abundance of epibenthic echinoderms at seafloor photography station M21/4_250. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 17 records from Analyses of the recent components of sediment core PS1400-4. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7010 records from La familia Asclepiadaceae en México. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 3 records from Registros de la babilla (Caiman cocodrilus) asociados al Proyecto: Correlación entre nivel de testosterona, territorialidad y éxito reproductivo. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 39 records from Swedish Malaise Trap Project (SMTP) - Formicidae. 373 records from Otter survey of Ireland 2004 & 2005. 1473 records from Royal Belgian Institute of Natural Sciences Bryozoa collection. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 763 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 124 records from Birdrace-LohmannsAdleraugen-Münster. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 328027 records from All taxa records for Leicestershire and Rutland. 167 records from Données naturalistes de NOËL Rémi. 542 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 205 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 163 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 14 records from Two new species of Balacha (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from Brazil with comments on their phylogenetic position and biogeography. 1 records from La Côte oubliée - La Planète Revisitée - Nouvelle-Calédonie 2017. 1413 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 222 records from (Table C a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-23 at 3000 m water depth. 61 records from Alien Species in Poland - Plants. 1733 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 398 records from Sistemática del género Polianthes L (Agavaceae). 1411 records from Distribution of planktic foraminifers of core Y71-09-101. 1 records from Taxonomic revision of the genus Lycenchelys (Osteichthyes: Zoarcidae) in Japanese waters. 42 records from A new species of the grass-feeding leafhopper genus Amblysellus Sleesman (Hemiptera: Cicadellidae: Deltocephalinae) from western Mexico, with a checklist and key to species. 323 records from Données de VINCENT Alexis (SAPROX). 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 689 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 8 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 895 records from Geometridae de France métropolitaine. 256 records from Cactophilic Drosophila and Opuntia. 2 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 44560 records from WCPS Bird Survey Project. 1 records from Planktic foraminifera abundance of Hole 4-26. 106 records from Sylter Meerstrandläufer. 717 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 3 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 31913 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 2012 records from Pollen profile RAC20, Lake Racou, France. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 4 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 2611 records from NEON Biorepository Carabid Collection (DNA Extracts). 225 records from Tillegg Røtinga i Os. 27 records from Données naturalistes de Franck MERLIER. 192 records from Total foraminifera counts of multinet M10/2_MSN218. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1338 records from (Table 9) Distribution of planktonic foraminifers in ODP Site 112-687. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 1 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 103418 records from MSB Fish Collection (Arctos). 16 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 21346 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 333 records from Langes Tannen (Uetersen). 249 records from Content of different diatom species in sediment core GIK23259-2. 1159 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 2247 records from Churchyards for London. 8 records from Aktion des Romain-Rolland-Gymnasiums. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 25 records from Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species. 12 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 710 records from Chronicle of Nature - Phenology of Fishes of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 17 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 3 records from Integrative taxonomy of Thalerosphyrus Eatonı 1881 (Ephemeropteraı Heptageniidae) in Thailand. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 364 records from Benthic foraminifera counts of sediment core GIK17730-4. 19 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 1109 records from Banco de Germoplasma de Especies Nativas del Instituto de Ecologia y Ambiente Humano - UNSA- Arg. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 123 records from City of Edinburgh Natural Heritage Service - Hillend Wildflower Meadow Survey. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 12595 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 135 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1877 records from Odonata de la huasteca potosina (insecta). 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 21 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 111 records from Données naturalistes de Mr MONTAGNER Sylvain. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68910 records from Données de l'Observatoire de la Faune de Bourgogne. 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 34 records from Planktic foraminifera counts of sediment core V19-19. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 1015 records from Monitoreo de aves en la zona del Anchicaya (Colombia, Valle del Cauca, Buenaventura) en el marco del Convenio de Investigación Icesi/Celsia. 765 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 111 records from Total foraminifera counts of multinet POS247/2_MSN1388. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 298 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 197 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 1 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 84 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 920750 records from Texas A&M University Insect Collection. 214 records from Insectarium René-Martineau (IRM). 3139 records from Palynological investigation of profile Tso Kar. 35198 records from Herbarium of Shinshu University. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 710 records from Cepora butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 213204 records from KUBI Herpetology Collection. 1168 records from Foraminifera, sedimentological parameters and sea surface temperature and salinity calculated on core SO82_5-2. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 116 records from Programme ACT : Répartition Perdrix rouge 2004 - 2008 Coordonnées GPS Lambert 93. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 163 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200590. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 24 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 158 records from Nannofossil abundance of Hole 59-448. 6873 records from Monitoring of the intertidal biodiversity of rocky beaches with schools in Portugal 2005-2010. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 4 records from Planktic foraminifera abundance of Hole 54-423. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 66 records from Calcareous dinoflagellates nominated in grain fraction < 20 µm. 182 records from Colección Invertebrados-Museo de Historia Natural Unillanos. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 2 records from Heteropterys rosmarinifolia, a new species of Malpighiaceae with verticillate leaves from savannas grasslands of central Brazil. 30 records from Microplankton counts and carbon biomass at station TT008_5-CTD42. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 342 records from Données opportunistes de Mammifères marins SPM de 1997 à 2007 récoltées par le RNE et le Baleineau de SPM de 1997 à 2007. 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 10 records from New species of Rivudiva Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) with comments on R. minantenna Lugo-Ortiz & McCafferty and R. trichobasis Lugo-Ortiz & McCafferty. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 5656 records from microbial diversity Raw sequence reads. 26 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 26 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 10 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 7407 records from Dipterists Forum: Field Week 2018 (Stoke). 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 15491 records from Waterway Survey. 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 4 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 7076556 records from Great Backyard Bird Count. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 13 records from Warnowufer Groß Klein. 109 records from Planktic foraminifera abundance of Hole 18-181. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 68 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1387. 18540 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from Two new Kukri Snake species (Colubridae: Oligodon) from the Nakhon Si Thammarat Mountain Range, and addition of O. ocellatus to the fauna of Thailand. 3822 records from (Table T2) Dinoflagellate stratigraphy of ODP Hole 184-1148A. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 464 records from Flora vascular y no vascular: expedición Rabanal - Proyecto Boyacá BIO UPTC. 24 records from Peces de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 639 records from Chronicle of Nature - Phenology of Mammals of State Nature Reserve Olekminsky. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 248 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 1596 records from Parque Nacional Natural Sanquianga, monitoreo veda de camarón. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 39 records from Soolbach-Tal. 98 records from Registros de peces y cetaceos en el marco del proyecto Ocurrencia, distribución, estado genético y de contaminantes de los cetáceos de La Guajira. 349 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_100MC. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Description of a new species of the genus Paraedes (Diptera: Culicidae) in Assam, India. 74 records from SuLaMa reptile monitoring. 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 11 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24493 records from Plan de vertebrados de la Patagonia. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 2 records from Occurrence of mammalia relicts at site Igstadt I. 4155 records from Données naturalistes de Nathalie POT. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 65 records from Macrofauna abundance in surface sediment sampled during cruise DI226. 20 records from Five new species and a new record of Sathytes Westwood from eastern China (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 51301 records from Biodiversity4all Research-Grade Observations. 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 977 records from Observation records of Amphibians. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 33 records from Evaluación del efecto de esponjas arrecifales en el asentamiento larval de corales escleractinios. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 9 records from Nannofossil abundance of Hole 2-11. 1910 records from Pollen profile from sediment core AV14_K2-3. 122 records from Scottish Beaver Trial incidental species records. 631 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part II. 2 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 1870 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 100 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 3 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 4476 records from Benham Rise 16S raw sequence reads. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1705 records from 16S rDNA metagenomes of Western Balkans glacial lakes sediments. 13 records from New species of Tingidae (Insecta: Heteroptera) from Madagascar. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 72 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 7822 records from Bryophytes specimens of Akita Prefectural Museum. 30 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 1362 records from Range table from benthic foraminifers in ODP Hole 141-861C. 1288 records from Range table from benthic foraminifers in ODP Hole 159-959D. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 182 records from Total foraminifera counts of multinet M21/2_MSN652. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 39 records from Planktic foraminifera abundance of Hole 14-137. 3 records from Revisión del género Microogenius Gutiérrez (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), con descripción de dos nuevas especies altoandinas. 2493 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 6 records from Microplankton counts and carbon biomass at station TT007_3-CTD29. 124 records from Wiesenbiotop am Wasserturm. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 1321 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 2510 records from CAS Entomology Type (TYPE). 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 5 records from Five new species of the genus Primulina (Gesneriaceae) from Limestone Areas of Guangxi Zhuangzu Autonomous Region, China. 244 records from Sponges of the Guyana Shelf. 510 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 119 records from Kinorhyncha. 10786 records from MBML-Anfibios - Coleção de Anfíbios MBML. 2984 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 2250 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 615 records from Marine subseafloor sediment Targeted Locus (Loci). 1 records from Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham. 3 records from Notes on the genus Echinops L. (Asteraceae) in SE Europe. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 3 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 70546 records from Nutrient addition mesocosm experiment Targeted Locus (Loci). 130 records from Total foraminifera counts of multinet M21/6_MSN784. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 7121 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 9210 records from SuLaMa bird occurence data. 2 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 58 records from Ostracoda abundance of Hole 42-372. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 3579 records from Amphibian and reptile records for Great Britain 2016-2019. 385 records from (Appendix 3) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD99-2341. 10 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 118 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 5 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 23648 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 20 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 126 records from Regionalpark(Hattersheim). 131 records from Foraminifera abundance of sediment core BM1958.631. 108 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 59 records from Benthic foraminifera abundance of Hole 84-569A. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 2 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 9680 records from herbarium_database. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 1200 records from Monocotyledonous Geophytes of Fergana Valley. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 12 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 86 records from UWIZM Cnidarians. 130 records from Nannofossil abundance of Hole 9-84. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 59737 records from Taiwan Forestry Research Institute. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 25 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras (Oeceoclades_los_tuxtlas). 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 174667 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 15205 records from UAM Invertebrate Collection (Arctos). 1 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 1 records from Review of Neoanchisquilla Moosa, 1991 and Neclorida Manning, 1995 (Crustacea: Stomatopoda: Squilloidea), with descriptions of two new species of Neoanchisquilla from the Indian Ocean. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 12 records from Chronicle of Nature - Phenology of Amphibia of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 342 records from Abundance of macroinvertebrates in sites with varying degradation levels in Lake Wamala. 638 records from (Figure 2) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-762B. 8 records from A new genus and eight new species of tail-wagger snails from eastern South Africa, with a key to genera within Sheldonia s. l. (Gastropoda: Urocyclidae). 6 records from Three new species of Poecilosclerida (Porifera, Demospongiae, Heteroscleromorpha) from the Aleutian Islands, Alaska. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 18 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 190 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 10 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 125 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 1146 records from Bryophytes, fungi and lichens on dead wood. 8 records from On two enigmatic spiders (Araneae: Cybaeidae & Phrurolithidae) from the Russian Far East. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3472 records from Microhabitat distribution of arboreal oribatid mites (Oribatida), associated with the Siberian pine (Pinus sibirica) of Western Siberia.. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 83 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 14755 records from Collection Pisces SMF. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 39872 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 5217 records from NZCS Brownsberg Nature Park Camera trap Monitoring 2013-2015. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1538 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 14517 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 260 records from Учет следов по первому снегу (Белая тропа). 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 34 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 4077 records from SOPTOM_2017_12_18. 183 records from Oribatid mite communities (Acari: Oribatida) in different habitats of the Polistovsky Nature Reserve (Pskov Region, Russia). 941 records from Programme ACT : Répartition Pigeon ramier 1996 - 2000 Coordonnées GPS Lambert 93. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 10 records from Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records. 4 records from Benthic macrofauna abundance of sediment core 12930-017. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 756 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 286 records from (Table 1) Planktonic foraminiferal abundance at DSDP Site 94-606. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 178 records from Corn bunting surveys on the Western Isles. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 6 records from Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia. 345 records from Kimberley Islands Biodiversity Survey (Bats). 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 7050 records from Plot-based observations of macrofungi in raised bogs in Western Siberia (2014-2020). 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10295 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 18 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 1978 records from Invasive Non-Native Species. 1046 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 16506 records from Database for alien invasive plants occurrences in Germany. 181 records from Life cycle and production of Canuella perplexa (Copepoda, Harpacticoida) in the Sluice dock Oostende between 1976-1978. 2 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 3 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 699 records from Herbier de Strasbourg. 115 records from Strathclyde badger sett surveys 1996-2000. 341 records from (Table 7) Planktonic foraminifer abundance of ODP Hole 162-983A. 101 records from RISC Non-Native Species Records for Rhododendron Leafhopper. 26 records from Planktic foraminifera of sediment core GeoB1406-4. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 3673 records from Spider (NSMK-SP). 4160 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 13 records from Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840. 237 records from Données du/de la naturaliste Jeliazkov Aliénor provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1017 records from Programme ACT : Répartition Merle noir 2003 - 2007 Coordonnées GPS Lambert 93. 20 records from The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species. 29453 records from Manitoba Museum of Man and Nature. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 199042 records from Coral. 39380 records from Vascular plant diversity in forests. 11404 records from Caddisfly (Trichoptera) records from Britain and Ireland, via iRecord. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 975 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 167158 records from KUBI Mammalogy Collection. 92 records from Nottekanal, Klasse 7 - 10. 2 records from Review of freshwater Bryozoa (Phylactolaemata) of Central Africa with descriptions of two new species. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 4733 records from Inventaire des Mollusques Sphaeriidae de France. 4682 records from Live benthic foraminifera in South Atlantic surface sediments. 16885 records from données aranéologiques de CORNIC Jean-François. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 1280 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 12 records from Description of a new species of Pagurus Fabricius, 1775 (Crustacea: Paguroidea: Paguridae) from the Pacific coast of Costa Rica, Central America, with notes on Pagurus albus (Benedict, 1892). 107 records from 1st Austrian Birdrace (Wien). 6 records from A review of the gall midges (Diptera: Cecidomyiidae) of Indonesia: taxonomy, biology and adult key to genera. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 238 records from (Table S6) Pliocene/Pleistocene benthic foraminiferal abundances from sediment core KR9912PC4. 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 3 records from Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 1 records from Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea. 1727 records from TWIC Record a Raptor Survey. 958 records from Epifitas del piedemonte de Yopal. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 4 records from Sächsische Schweiz (Wehlener Gebiet). 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 64 records from Nannofossil abundance of Hole 7-63A. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 72 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 14 records from Neue Arten der Gattung Atomaria STEPHENS, 1830 aus der Türkei und dem Irak (Coleoptera, Cryptophagidae). 4461 records from MfN - Fossil vertebrates IV. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 4 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 3231 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 1607 records from MEXU/Flora de Oaxaca. 37931 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 3483 records from Arthropod fauna in christmas tree plantations. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 24 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 72 records from Données du naturaliste Mael Garrin. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2933 records from Données naturalistes d'Alain BERLY. 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 94 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1380. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 3 records from New species of Australopericoma Vaillant (Diptera: Psychodidae) from the Brazilian semiarid region and key to males of the genus. 1753 records from Herbarium of the Prioksko-Terrasnyi Biosphere Reserve. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 12719 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 1 records from First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species. 637617 records from Données de la flore d’Alsace (SBA). 571 records from Collection Aves (bird skeletons) SMF. 184 records from Synthèse de la Répartition des populations de mouflon méditerranéen en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 35 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 37 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 8 records from Diversidad de bacterias fotótrofas en comunidades microbianas bentónicas de Bahía Concepción, BCS, México. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1098 records from Données opportunistes sur les rhopalocères. 161 records from Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia. 57 records from Total foraminifera counts of multinet M21/4_MSN718. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from On two genera of spiny Pudicinae (Nematoda: Trichostrongylina) parasites of the spiny rat Proechimys simonsi (Mammalia: Echimyidae) from Peru. 7327 records from Pseudoscorpion Recording Scheme of the UK. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1555478 records from Flore Franco-Belge. 16560 records from EAC - Herbário Prisco Bezerra. 56 records from Nannofossil abundance of Hole 37-332B. 39 records from Suivi des reptiles en forêt du Madrillet. 38 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 2 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 197 records from Radiolaria assemblage in sediment core GIK17722. 11298 records from Données du naturaliste DEHALLEUX Axel provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions. 72 records from Phytoplankton abundance at station Rigel_3_2005-02 in Febraury 2005, Chipana, Chile. 1975 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 145 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 2740 records from Olga Lakela Herbarium, University of Minnesota Duluth. 34 records from Earthworms population in old-growth taiga forests of Pechoro-Ilych State Nature Reserve. 44 records from Leegmoor (Moormerland/Leer). 9409 records from Collection Crustacea - ZMB. 740 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 11815 records from Herbario CTES Plantas Vasculares. 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 158 records from Total foraminifera counts from multinet M31/3_MSN914. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from A new species of the thorid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the deep sea of the Northwestern Pacific Ocean. 33 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 3446 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 72142 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 1357 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 8386 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 19006 records from Weevil and Bark Beetle records via iRecord. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 239 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco (Hospederos). 1737 records from Collembola of broadleaved forests along gradient of urbanization in Moscow. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 351418 records from Plantae of Costa Rica (INBio). 2 records from A new species of the genus Lamellitettigodes (Orthoptera: Tetrigidae) from PR China, with taxonomic notes on the genus. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 14950 records from Skandobs. 2 records from The webspinning sawfly genus Neurotoma (Hymenoptera, Pamphiliidae) of South Korea: Neurotoma silla sp. nov. and a key to species. 148 records from Annelida collection of National Museum of Nature and Science. 2 records from What are the smallest moths (Lepidoptera) in the world?. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 66 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 3066 records from Carnarvon Basin upland survey. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 15 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 14491 records from 16S_Sediment_Bolinao. 516 records from Range table from benthic foraminifers in ODP Hole 172-1055C. 2032 records from (Table T1) Census counts of planktic foraminifers at ODP Hole 175-1087A. 1711 records from Análisis de Integridad Biológica para el Parque Natural Regional Páramo del Duende. Convenio CVC- Univalle 108 de 2017. 328 records from Length and weight of Antarctic Rock Cod (Trematomus bernacchii) from sites adjacent to Davis Station 2012/13. 5027 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 213 records from Phenological Center - Mushrooms (Arkhangelsk). 2 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 123 records from Resilience of Antarctic marine benthic invertebrates and the ecological consequences of environmental change - Amphipod Data 2002/10. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 389 records from Données espèces - Expertise IQE 89. 1000 records from Hoverflies (Syrphidae) of Ireland. 189 records from Impact of offshore oil drilling operations on the diversity of marine benthic Foraminifera - Raw sequence reads. 6652 records from Inventory of plant species through Benin (West Africa). 372 records from (Table T5) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1052E. 4109 records from South Caribbean Diversity. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of the alpheid shrimp genus Automate de Man, 1888 (Decapoda: Caridea) from Japan. 6431 records from Anfibios y reptiles del estado de Tamaulipas, México. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 445 records from Inventory of Tragelaphus spekii in southern Benin. 1451 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 1226 records from Suivis télémétriques des Otaries des Kerguelen par le Centre d'Etudes Biologiques de Chizé. 602 records from Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 585 records from Livingstone Museum Bat Collection. 12 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 198 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 16 records from Traumatomutilla André miscellanea: Revision of the bellica, bifurca, diabolica, and vitelligera species groups, and a new group for the new species T. pilkingtoni Bartholomay and Williams (Hymenoptera: Mutillidae: Sphaeropthalminae: Dasymutillini). 175 records from Range table from planktonic foraminifers in ODP Hole 175-1083A. 20094 records from Microbial community in PAH-contaminated riverine sediments. 14769 records from Rådgivende Biologer. 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 1 records from Two new species of Comesomatidae (Nematoda) from the East China Sea. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 44 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 34 records from Total foraminifera counts of multinet M21/4_MSN722. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 2375 records from Regroupement de données Odonates. 786 records from Planktic foraminifera abundance of Hole 23-219. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 97 records from POPA- Fisheries Observer Program of the Azores: Sea turtle sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 2 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 241 records from Bird Banding Data for Cockscomb Basin Wildlife Sanctuary, Belize 2016 - 2017. 2 records from Two new species of the genus Chironephthya (Octocorallia, Alcyonacea, Nidaliidae Siphonogorgiinae) from the Gulf of Thailand. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 9 records from New distribution records of the genus Saga Charpentier, 1825 (Orthoptera Tettigoniidae: Saginae) from Iraq. 76 records from Inventaire hivernal des nids de frelon asiatique. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 865 records from Phytoplankton abundance measured on water samples from rivers of the Lena Delta in 2009. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 12652 records from Bell Museum fungi. 165 records from EDP Foz-Tua: Terrestrial Birds (occasional observations)- Complementary Studies [2009-10]. 892 records from Trap data WR2, 599 m. 2 records from Colletes alborzensis nov. sp., a new bee species from Iran (Hymenoptera, Colletidae). 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 98 records from Occurrence of mammalia relicts at site Koziarna Cave. 39159 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 401 records from Planktic foraminifera distribution of sediment core SU81-07. 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 51 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 8 records from Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus. 46 records from Aktion Wiese und Wegrain Gitzenheide. 122 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 2779 records from Invertebrates compiled by W.Block. 708 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 132 records from Insect (HUNM-IN). 175 records from Données naturalistes de Monsieur VILAIN Frederic. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 3032 records from Fishes in MZNA-VERT: interactions between signal crayfish and fish communities. PhD project, Iván Vedia. 177 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 306-U1313. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59978 records from Données naturalistes de Monsieur François FOURNIER. 129 records from Planktic foraminifera abundance of Hole 72-515A. 612 records from Nannofossil abundance of Hole 29-277. 444 records from Phenology of Crocus. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 30 records from Range table from ostracoda in ODP Hole 151-910A. 14368 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 5 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 27487 records from UAZ Mammals. 23 records from Viviendo en los Andes: registros notables de la distribución altitudinal del oso andino, Tremarctos ornatus (Ursidae) en Boyacá, Colombia. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 316 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001E. 6 records from Geothermal Fumarole Subsurface Mt. Erebus, Antarctica. 72 records from Données Réseau National d’Échouages de Saint-Pierre et Miquelon. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 336 records from Malawi-Saturniidae-Biodiversity-Data. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 324892 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 20 records from Phenological Center - Fishes (Arkhangelsk). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 14533395 records from Southern African Bird Atlas Project 2. 195 records from Bird specimens of Obihiro Centennial City Museum. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1462 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 28029 records from Seasearch Marine Surveys in the Channel Islands. 98 records from Etude d'impact de la ZAC Bellevue - compléments. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 698 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 21 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 55601 records from Fish Specimens. 24 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 11686 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 4 records from Two new species of the genus Scaphidium Olivier (Coleoptera: Staphylinidae Scaphidiinae) from Southwest China. 9 records from Distribution of planktic foraminifera of sediment core GIK23352-3 at stadium 5.5. 57 records from Abundance of benthos infauna at station GIK23006-3. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 770 records from Nivå Bay species list, Zealand, Denmark. 4 records from Plectranthias cruentus, a new species of anthiadine perchlet (Teleostei: Serranidae) from the Lord Howe Rise, Tasman Sea. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 4108 records from VIC - Herbário da Universidade Federal de Viçosa. 25 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 4 records from A new species of Carpenter Moths (Lepidoptera, Cossidae) from Tarbagatai (NE Kazakhstan) and Altai (SW Siberia, Russia) Mountains. 27 records from Annotated checklist of the endemic Tetrapoda species of Iran. 206796 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 148794 records from Arctic Ocean Diversity. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Biotop Alexander-von-Humboldt-Schule. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 591 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 408 records from Données naturalistes de Jean-Michel LEMAIRE. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 652 records from Spider species diversity from wet and dry habitats. 53 records from CHAS Botany Collection (Arctos). 67 records from Berkeley subregion mammals. 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 278 records from Investigación prioritaria hacia el conocimiento y conservación de tortugas amenazadas del bosque seco tropical colombiano Mesoclemmys dahli (Carrachina) y Chelonoidis carbonaria (Morrocoy). 11 records from A revision of Pinobius. II. Three new species from Cambodia and Indonesia, and additional records (Coleoptera: Staphylinidae: Paederinae). 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 261 records from Programme ACT : Répartition Alouette lulu 2007 - 2011 Coordonnées GPS Lambert 93. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 35 records from Total foraminifera counts of multinet FCA97C_MSN1343. 126 records from Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 1832 records from Invasive Alien Species in Denmark. 52 records from Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Motzener Tonsee. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 78 records from Range table from benthic foraminifers in ODP Hole 159-960C. 10 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 6782 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from A review of the genus Paratus Simon (Araneae, Dionycha). 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1694 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1288 records from Barcant Butterfly Collection - Nymphalidae. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB05 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 130434 records from Herbarium of Taiwan Forestry Research Institute. 195 records from Phytoplankton abundance at station CD47_1206C#7. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 426 records from Planktic foraminifera abundance of Hole 7-64. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 4 records from Two new species of Aufidus (Hemiptera, Cercopidae) from New Guinea. 18 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 47 records from The grasshoppers (Orthoptera, Acridomorpha) from the Mitaraka Mountain Range, French Guiana. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 2751 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 63 records from Nannofossil abundance of Hole 94-609C. 231 records from Marine sediment metagenome ICM_CFU. 1 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 547 records from arthropods on Plantago lanceolata. 30242 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 5 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 5855 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 79122 records from University of New Mexico Herbarium. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 18821 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 3 records from Three new species of entimine weevils in Early Miocene amber from the Dominican Republic (Coleoptera: Curculionidae). 239296 records from HO AVH data. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 56 records from Total foraminifera counts from M35/1_MSN1075. 688 records from données arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 5 records from Nannofossil abundance of Hole 6-58. 34 records from Planktic foraminifera counts at CTD station PS55/084-1. 4 records from Nannofossil abundance of Hole 3-22. 670 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 5468 records from Industry Sea Lice Counts at BC Marine Finfish Aquaculture Sites, 2020 and Ongoing. 32 records from A review of Stephanidae (Hymenoptera: Stephanoidea) from India, with the description of five new species. 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 1032 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 134 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 7 records from The Neotropical genus Cyriocosmus Simon, 1903 and new species from Peru, Brazil and Venezuela (Araneae: Theraphosidae: Theraphosinae). 127 records from Programme ACT : Répartition Pigeon colombin 2001 - 2005 Coordonnées GPS Lambert 93. 1631 records from Phragmites of Canada. 92 records from Additional Milicia excelsa occurrences in Benin. 6480 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 27 records from Nannofossil abundance of Hole 11-105. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 1080 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 29 records from Berkeley subregion bats. 292317 records from Oiseaux de France métropolitaine 2009-2013 en période hivernale. 203 records from Percentages of planktonic foraminifera species in sediment core V30-51. 216 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 2 records from Integrative description of two new Cratena species (Mollusca: Nudibranchia) from western India. 3 records from Données naturalistes de CARBUCCIA Benjamin. 11916 records from UCSC - Kenneth S. Norris Center for Natural History, University of California Santa Cruz, Herbarium. 1 records from Zorotypus huangi sp. nov. (Zoraptera: Zorotypidae) from Yunnan, southern China. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 1683 records from Données naturalistes de Brice DEREPAS. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 26350 records from JCT AVH data. 13769 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 4 records from Abundance of nematoda in sediment profile M3/1_035 from the Iberian deep sea basin (Table 5). 2 records from A new species of Goniacerini from Cameroon (Coleoptera: Staphylinidae: Pselaphinae). 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 33 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 58 records from Schulgarten Zinnowwald-GS. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 6 records from New sciaphilic plakinids (Porifera, Homoscleromorpha) from the Central-Western Pacific. 31 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 19 records from Polysyncraton (Ascidiacea, Didemnidae): a re-examination of some specimens and descriptions of three new species. 28573 records from Royal Belgian Institute of Natural Sciences Mollusc collection. 235 records from The ecology of Najas flexilis (Slender naiad). 167 records from The Geometridae of Ethiopia III: genus Zamarada (Lepidoptera: Geometridae Ennominae, Cassymini). 3224 records from Amphibiens de Guyane. 134 records from Nannofossil abundance of Hole 7-62A. 57 records from Colección biológica viva de primates monos nocturnos (Aotus l. griseimembra) - FUCEP- Valle del Cauca - Cali. 1 records from Micropygomyia (Coquillettimyia) nahua sp. nov., a new Phlebotominae sand fly from Mexico (Diptera, Psychodidae). 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Nannofossil abundance of Hole 9-82. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 8 records from Revisão do gênero Antiteuchus Dallas (Heteroptera, Pentatomidae, Discocephalinae). 145 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 110 records from Total foraminifera counts of multinet M21/3_MSN662. 199234 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification certaine. 5 records from Collection Myriapoda - SNSD. 241 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 24630 records from Successional trajectories of coastal bacterioplankton communities in response to co-exposure of cadmium and phenanthrene. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 24 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 60 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 469 records from La liste (3) Rouge des plantes menacées de la Guinée. 58 records from Synopsis of the carpenter bee subgenus Xylocopa (Schonnherria) Lepeletier, 1841 (Hymenoptera: Apidae) in Colombia, with designation of lectotypes and the description of two new species. 212 records from Am Moosangerweg. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 22 records from (Table 2a) Species of planktonic foraminifera found in sediment traps at Station Vy20-3217TR. 4428 records from Stratigraphic occurrence of selected marine palynomorph species recorder in the Paleogene of ODP Hole 105-647A (Table 3). 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 345 records from RV Investigator Voyage IN2016_V06 Seabird Observations, Australia (2016). 437 records from (Table 5) Distribution of foraminifera in the Miocene section of ODP Hole 133-826A. 96 records from Foraminifera species abundances from tow TT011_9-MOC69. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 35 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 14 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo (UADY). 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 3 records from First record of the genus Microstenus Szépligeti (Hymenoptera: Ichneumonidae Cryptinae) from China, with description of one new species and a key to world species. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 67 records from R-Fungi - Herbário do Museu Nacional. 3546 records from Dorset SW Pilot species dataset. 2 records from Three new earthworm species of the tokioensis - group in the genus Amynthas (Oligochaeta: Megascolecidae) from Guangxi Province, China. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 36635 records from LSUMZ Mammals Collection. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 219 records from Type Specimens Of Birds In The American Museum Of Natural History Part 12. Passeriformes: Ploceidae, Sturnidae, Buphagidae, Oriolidae, Dicruridae, Callaeidae, Grallinidae, Corcoracidae, Artamidae, Cracticidae, Ptilonorhynchidae, Cnemophilidae, Paradisaeidae, And Corvidae. 585 records from Survey data of rocky shores on the Monitoring sites 1000 project, BDCJ. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune écrasée. 212 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 1000 records from nsmk_mm_2019. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 558015 records from New York City Street Tree Census - 2005. 982 records from Diatom assamblage in samples from sediment trap OG4. 765 records from DAR AVH data. 170543 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 2 records from Rediscovery and re-description of Rhaphaulus assamicus Godwin-Austenı 1886 ı an endemic pupinid land snail from India (Gastropoda: Pupinidae). 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 12003 records from marine metagenome Raw sequence reads. 860 records from Vachellia caven in Southern South America. 285 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V12-122. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 14 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 1 records from Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus.. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from Review of the fish genus Epinnula Poey (Perciformes: Gempylidae), with description of a new species from the Pacific Ocean. 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 8 records from Three new subterranean species of Baezia (Curculionidae, Molytinae) for the Canary Islands. 4494 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 488 records from Foraminifera abundance of Hole 18-176. 108 records from BIRDRACE Diesmal sehen wir mehr. 610 records from EDP Foz-Tua: Lichen flora – Complementary Studies [2011] and Ecological Monitoring Program [2012-2015]. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 2 records from A new species of the genus Fernandezina Birabén, 1951 (Araneae: Palpimanidae Otiothopinae) from Colombia. 26 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and speci
Keywords: GBIF; biodiversity; species occurrences